2020
DOI: 10.1186/s42358-020-00127-7
|View full text |Cite
|
Sign up to set email alerts
|

Hylan G-F20 and galactomannan joint flares are associated to acute synovitis and release of inflammatory cytokines

Abstract: Background: Injection of Hylan G-F20 (HY) into joints may provoke local flares, which mechanisms may involve reaction to protein contaminants. We have previously developed a protein-free saline-soluble galactomannan derived from guar gum (GM) that displays both analgesia and chondroprotection in experimental osteoarthritis (OA). We now demonstrate that both GM and Hylan G-F20 (HY) promote mild synovitis with cytokine release after intra-articular injection. Methods: Mice received 100 μg/25 μL GM or HY or salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Nociceptive behavior was assessed using the electronic pressure meter nociception paw test by an observer blinded to group allocation ( 28 ). Animals were placed in acrylic cages (12 × 10 × 17 cm high) with a wire grid floor, 15 min before the beginning of the tests, in a quiet room.…”
Section: Methodsmentioning
confidence: 99%
“…Nociceptive behavior was assessed using the electronic pressure meter nociception paw test by an observer blinded to group allocation ( 28 ). Animals were placed in acrylic cages (12 × 10 × 17 cm high) with a wire grid floor, 15 min before the beginning of the tests, in a quiet room.…”
Section: Methodsmentioning
confidence: 99%
“…[62] Comparing PRP versus HA viscosupplements in terms of symptoms' relief and time for arthroplasty revealed that the first is associated with better outcomes and might prolong the time for arthroplasty and provide an effective therapeutic option in selected patients with knee OA not responding to conventional A B Reproduced under a Creative Commons Attribution (CC BY 4.0) license. [53] Copyright 2020, The Authors. Published by Springer Nature.…”
Section: Biomaterials and Viscosupplement-based Therapiesmentioning
confidence: 99%
“…After 2 months of VS, patients with knee OA previously treated with opioids or IA CS injections exhibited a statistically significant decrease in medication. [ 52 ] Another study on Hylan G‐F20 (HY) demonstrated that both protein‐free saline‐soluble galactomannan derived from guar gum (GM) and Hylan G‐F20 (HY), besides exposing both analgesia and chondroprotection in experimental OA, yield mild synovitis with cytokine release after IA injection [ 53 ] ( Figure ). A study on the long‐term survivorship after 5 years of IA injection of high‐molecular‐weight HA (GF‐20, Synvisc‐One) demonstrated a significantly longer duration of clinical benefit, representing an opportunity to delay the arthroplasty procedure.…”
Section: Biomaterials and Viscosupplement‐based Therapiesmentioning
confidence: 99%
See 2 more Smart Citations